PROBLEMATIKA GURU DALAM PEMBELAJARAN BERBASIS TIK DI ERA GLOBAL - I Made Ariasa Giri (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
The current model of learning is still transmissible, it affects the learning outcomesachieved. In general there are still many students who do not reach the value of KKM that hasbeen established school. The influence of ICT in the learning process has changed the paradigmof learning from teacher centered to student centered. Teachers as initiators of education mustbe able to follow the global flow and ICT control. This suggests that the learning process shouldemphasize student activity in learning. The application of ICT in learning which by some expertopinion gives a big impact on the progress of education will not be useful if the implementationis not well designed by the teacher. ICT-based learning activities are generally structured toassist in building concepts, knowledge procedures and expressing student expression in learning.The rapid development of information technology in the current era of globalization and itsdevelopment has influenced the world of education. Global demands require the world ofeducation to always adapt technological developments to efforts in improving the quality ofeducation, especially the adjustment of the use of ICT for teachers, especially in the learningprocess that makes learning become meaningful.Keywords: Teacher Education Problematic, ICT Learning